EFFECTIVITY OF ROSELLE EXTRACT (Hibiscus sabdariffa L.) AS A TREATMENT FOR HYPERLIPIDEMIA - Chairunnisa, Nurul Hidayah (Majority, 2015)
Abstract Roselle (Hibiscus sabdariffa L.) is a well known plant which has been used for a long time by people in Indonesia. Every part of this plant is very useful, for example as a treatment to decrease the level of cholesterol. Some researches found that the effectivity of roselle extract is the same as antihyperlipidemic drugs. One of the research stated that the ethanolic extract of roselle’s leaves and calyces in 500mg/kg/day dose effectivity is almost the same with Lovastatin in 10mg/kg/day dose. Another research showed that the ethanolic extract of roselle’s leaves in 200 and 300mg/kg/day dose effectivity is the same as Atorvastatin in 10mg/kg/day dose to decrease cholesterol level. Keywords: antihyperlipidemic, calyces, cholesterol, leaves, roselle. Abstrak Rosella (Hibiscus sabdariffa L.) merupakan tanaman yang telah dikenal secara luas dan telah lama pemanfaatannya oleh masyarakat di Indonesia. Setiap bagian dari tanaman ini sangat berguna, contohnya sebagai obat penurun kolesterol. Beberapa penelitian menemukan bahwa efektivitas ekstrak rosella sama seperti obat antihiperlipidemia. Sebuah penelitian menyebutkan ekstrak etanol kelopak bunga dan daun rosella pada kadar 500mg/kg/hari hampir sama efektifnya dengan Lovastatin 10mg/kg/hari. Penelitian lain menemukan ekstrak etanol daun rosella dengan dosis 200 dan 300mg/kg/hari sama efektifnya untuk menurunkan kolesterol seperti Atorvastatin 10mg/kg/hari. Kata kunci: antihiperlipidemia, daun, kelopak bunga, kolesterol, rosella.